TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN DALAM PERSPEKTIF FILSAFAT PANCASILA - Ramdhan, Mochamad Isnaeni (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
The awareness towards Environment and Social Responsibiltyexist and is a necessity for Indonesia, because ideologically,based upon Pancasila, Indonesian people has acquired theharmonization among live components of the universe, amongthe human environment and natural environment, among thehuman relationship as an individual and as a member of socialcommunity. That awareness has to be regulated systematicallyso that Environment and Social Responsibilty can beimplemented by and for whole Indonesian people.